Effect of water supply on canopy temperature, stomatal conductance and yield quantity of processing tomato (Lycopersicon esculentum Mill.) - Helyes, L.; Bőcs, A.; Pék, Z. (International Journal of Horticultural Science, 2010)
Tomato (Lycopersicon esculentum Mill.) is one of the most extensively cultivated horticultural crops in the world.Water supply is important for yield quantity and quality. The aims of the present study were 1) to evaluate the canopy temperature and the stomatal conductance on processing tomato substances with different water supply, 2) to investigate the effect of different water supply on yield quantity. There were two irrigated treatments, one of them was the reguralry irrigated plant stand which got 333 mm water during investigated period, including the precipitation and the other was the cut off substance which means the irrigation (drip) was stopped at the beginning of the ripening process and there was a control as well which got 189 mm precipitation. The canopy temperature was measured row by row with a Raytek MX 4 type infrared remote thermometer. The stomatal conductance was measured by Delta-T AP4 type porometer. There were significant differences between the control and irrigated plants according to the water supply which was formulated the canopy values. The plants with a deficient water supply were decreased the transpiration rate, therefore its cooling effect didn’t show up. The regularly irrigated tomato plants’ yield exceeded the unirrigated ones more than twice. It is emerged from the study that the irrigation has a positive effect on the amount of the harvestable yield in this year type.